A heating power cable
By using crosslinking reactive additives and perfluoroalkyl structures in the sheath layer of the heat-tracking power cable, the problem of deterioration of the performance of the insulating layer of the cable in dielectric environments such as water, acid, alkali, and salt is solved, and the long-term stable use and performance improvement of the cable is achieved.
Patent Information
- Application Number
- CN202210950852.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-08-09
AI Technical Summary
When heat-tracing power cables are used in dielectric environments such as water, acid, alkali, and salt, the performance of the insulating layer deteriorates rapidly, causing cable failure and affecting the performance of use.
The heat-tracing power cable design is adopted, including PTC core tape, insulating layer and sheathing layer. The sheathing layer is composed of materials such as neoprene, polyethylene, polyamide wax and reactive additives. The dispersion compatibility of the inorganic mixture is improved through cross-linking reaction, and the surface tension is reduced through perfluoroalkyl structure and hydrophobicity is improved.
Effectively protect the long-term use of cables in medium environments such as water, acid, alkali, and salt, which significantly improves the service life and performance stability of cables.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to a heating power cable. Background Art
[0002] Heat tracing has been widely used as an effective solution for pipe (storage tank) insulation and antifreeze. Its working principle is to dissipate a certain amount of heat through the heating medium and supplement the loss of the heated pipe through direct or indirect heat exchange to achieve the normal working requirements of heating, insulation or antifreeze.
[0003] The heating power cable is composed of a PTC core tape and an insulation layer. The flat tape made by extruding (or winding) the PTC material with uniform thickness and continuously on the parallel metal wire core (also known as the busbar) is the PTC core tape. A layer of polyethylene polymer or polyvinyl chloride insulation is wrapped on its outside; currently, heating power cables are often used in environments with water, acid, alkali, salt and other media. Moisture will cause the components in the inner and outer semi-conductive layers in close contact with the insulation layer to migrate or penetrate out, forming acidic or alkaline droplets at the interface between the insulation layer and the semi-conductive layer. Under the action of high electric fields, they will frequently hit the insulation surface, causing the performance of the power cable insulation layer to deteriorate rapidly and break down, and it is easy to be corroded and fail, which seriously affects the performance of the heating cable. Summary of the invention
[0004] In order to solve the technical problem mentioned in the background technology, the present invention provides a heating power cable.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A heating power cable comprises a PTC core tape, an insulating layer and a sheath layer; the PTC material is wound around parallel metal wire cores to form a flat tape, the PTC core tape is wrapped with an insulating layer, and the insulating layer is wrapped with a sheath material to form a sheath layer;
[0007] The sheath material is prepared by the following steps:
[0008] The chloroprene rubber, polyethylene, polyamide wax and plasticizer are mixed and added into an internal mixer, and mixed at 86-88°C for 2-4 minutes, and fillers, antioxidants and reactive additives are added, and mixed at 82-90°C for 4-5 minutes; then accelerators and vulcanizers are added, and mixed at 55-60°C for 2-3 minutes, and the jacket material is obtained after the material is discharged and cooled;
[0009] Further, the reactive additive is prepared by the following steps:
[0010] Step 1: Mix allyl 1H,1H-perfluorooctyl ether, glacial acetic acid, toluene and solid acid, heat to 60°C, add hydrogen peroxide, keep the temperature unchanged after the addition, continue stirring and reacting for 6 hours, cool after the reaction, wash with deionized water until neutral, separate the organic matter, and distill under reduced pressure to obtain a fluorine-containing auxiliary agent; under the action of glacial acetic acid, solid acid and hydrogen peroxide, oxidize the double bond in allyl 1H,1H-perfluorooctyl ether into an epoxy group to obtain a fluorine-containing auxiliary agent;
[0011] Step 2: Add aminopolysiloxane and fluorine-containing additive to isopropanol, stir and react at 80°C for 5 hours, then remove isopropanol at 0.01 MPa to obtain a reactive additive. The reactive additive is an organosiloxane containing a perfluoroalkyl group.
[0012] Furthermore, the molar ratio of allyl 1H,1H-perfluorooctyl ether, glacial acetic acid and hydrogen peroxide is 0.1:0.15:0.2; the mass ratio of allyl 1H,1H-perfluorooctyl ether, toluene and solid acid is 1:5:0.4; and the mass ratio of aminopolysiloxane, fluorine-containing additive and isopropanol is 8:1.6:15.
[0013] Furthermore, the PTC material is prepared by the following steps:
[0014] By weight, 30 parts of polypropylene, 30 parts of polyvinylidene fluoride, 3 parts of aluminum hydroxide, 3 parts of magnesium oxide, 6 parts of additives, 1 part of antioxidant MB and 1 part of antioxidant 168 are mixed evenly, and then 65 parts of carbon nanotubes are added for mixing. The mixing temperature is 190-200°C and the mixing time is 10-12min. Then, the PTC material is molded under a pressure of 185±5°C to obtain the PTC material.
[0015] Furthermore, the auxiliary agent is lauric acid and ethylene-vinyl acetate copolymer, and the mass ratio of the usage is 1:3. Lauric acid and ethylene-vinyl acetate copolymer can improve the dispersibility of conductive materials (carbon nanotubes) and inorganic materials (aluminum hydroxide and magnesium oxide), and the lauric acid and ethylene-vinyl acetate copolymer in the auxiliary agent have a synergistic effect, which can wet and penetrate the conductive material to remove air, and improve the low-temperature conductive performance and stability of the material.
[0016] Further, aminopolysiloxane is prepared by the following steps:
[0017] Under nitrogen protection, octamethylcyclotetrasiloxane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, octamethyltrisiloxane and tetramethylammonium hydroxide methanol solution were mixed, heated to 80°C, reacted for 12 hours, and then the vacuum degree was set to (-65)±5cmHg. The system was reacted under reduced pressure for 23 hours to remove small molecules and obtain aminopolysiloxane. The tetramethylammonium hydroxide methanol solution was prepared by mixing tetramethylammonium hydroxide and methanol in a ratio of 0.1g:10mL; the amount ratio of octamethylcyclotetrasiloxane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, octamethyltrisiloxane and tetramethylammonium hydroxide methanol solution was 100g:6g:1g:0.4mL.
[0018] Furthermore, the filler is a mixture of aluminum hydroxide, white carbon black and hydrotalcite in a mass ratio of 3:2:1. The chloroprene rubber used in the sheath material has excellent heat resistance and ozone aging resistance, but it contains chlorine and is a flame retardant rubber that extinguishes itself when away from the fire. However, it produces a large amount of black smoke when burned, and the released hydrochloric acid is severely corrosive and will cause secondary damage. Therefore, in the present invention, aluminum hydroxide, white carbon black and hydrotalcite are added as fillers, wherein the hydrotalcite can adsorb the generated acidic gas; aluminum hydroxide itself has flame retardant and smoke suppression effects, and white carbon black is a conventional reinforcing filler.
[0019] Furthermore, the plasticizer is polypropylene adipate with a molecular weight of 2500-3000; the antioxidant is antioxidant 1010; the accelerator is accelerator TMTD, and the vulcanizer is 2,4-dichlorobenzoyl peroxide.
[0020] Furthermore, by weight, the chloroprene rubber is 100 parts, the polyethylene is 10-12 parts, the polyamide wax is 6-9 parts, the plasticizer is 6-10 parts, the filler is 18-20 parts, the antioxidant is 1-2 parts, the reactive additive is 3-5 parts, the accelerator is 1-2 parts and the vulcanizer is 0.8-1 parts.
[0021] Beneficial effects of the present invention:
[0022] The present invention prepares a heating power cable, which includes a PTC core tape, an insulating layer and a sheath layer. The interior of the heating power cable is protected by improving the performance of the sheath layer. When preparing the sheath material of the sheath layer, a reactive additive is added. The reactive additive and the raw material can be cross-linked with the active groups on the surface of the filler (the surface of the filler generally contains hydroxyl groups) during the process of blending or extrusion. On the one hand, the dispersion compatibility of the inorganic mixture in the matrix can be improved, and the flame retardant and mechanical properties of the sheath material can be improved at the same time; on the other hand, the cross-linked structure as a part of the sheath material has a good bonding effect. At the same time, the hydroxyl groups of the reactive additive itself can also be cross-linked to form a continuous structure, which is hydrophobic and cooperates with the structure of the perfluoroalkyl group to effectively reduce its surface tension, showing excellent hydrophobicity and oleophobicity, and having good protective performance for cables that are in an environment of water, acid, alkali, salt and other media for a long time. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] A heating power cable comprises a PTC core tape, an insulating layer and a sheath layer; the PTC material is wound around parallel metal wire cores to form a flat tape, the PTC core tape is wrapped with an insulating layer, and the insulating layer is wrapped with a sheath material to form a sheath layer.
[0025] Example 1
[0026] Preparation of PTC materials:
[0027] According to weight, 30 parts of polypropylene, 30 parts of polyvinylidene fluoride, 3 parts of aluminum hydroxide, 3 parts of magnesium oxide, 6 parts of auxiliary agent, 1 part of antioxidant MB and 1 part of antioxidant 168 are mixed evenly, and then 65 parts of carbon nanotubes are added for mixing, the mixing temperature is 190-200℃, and the mixing time is 10-12min; then the PTC material is formed under the condition of 185±5℃. The auxiliary agent is lauric acid and ethylene-vinyl acetate copolymer, and the mass ratio of the amount is 1:3. The test resistivity is 0.42.
[0028] Comparative Example 1
[0029] Compared with Example 1, an auxiliary agent was added, and the other raw materials and preparation process remained the same as Example 1. The test resistivity was 0.79.
[0030] Example 2
[0031] Preparation of reactive additives:
[0032] Step 1: Under nitrogen protection, octamethylcyclotetrasiloxane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, octamethyltrisiloxane and tetramethylammonium hydroxide methanol solution are mixed, heated to 80°C, reacted for 12 hours, and then the vacuum degree is set to (-65) ± 5 cmHg. The system is decompressed for 23 hours to remove small molecules to obtain aminopolysiloxane. The tetramethylammonium hydroxide methanol solution is a mixture of tetramethylammonium hydroxide and methanol in the ratio of 0.1g:10mL; the amount ratio of octamethylcyclotetrasiloxane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, octamethyltrisiloxane and tetramethylammonium hydroxide methanol solution is 100g:6g:1g:0.4mL.
[0033] Allyl 1H,1H-perfluorooctyl ether, glacial acetic acid, toluene and solid acid are mixed, heated to 60°C, hydrogen peroxide is added, the temperature is kept constant after the addition, stirring is continued for 6 hours, and after the reaction is completed, the mixture is cooled, washed with deionized water until neutral, organic matter is separated, and a fluorine-containing auxiliary agent is obtained by vacuum distillation; wherein the molar ratio of allyl 1H,1H-perfluorooctyl ether, glacial acetic acid and hydrogen peroxide is 0.1:0.15:0.2; the mass ratio of allyl 1H,1H-perfluorooctyl ether, toluene and solid acid is 1:5:0.4;
[0034] Step 2: Add aminopolysiloxane and fluorine-containing additive to isopropanol, stir and react for 5 hours at 80°C, and then remove isopropanol at 0.01MPa to obtain a reactive additive. The mass ratio of aminopolysiloxane, fluorine-containing additive and isopropanol is 8:1.6:15.
[0035] Example 3
[0036] Preparation of sheath material:
[0037] 100 parts of chloroprene rubber, 10 parts of polyethylene, 6 parts of polyamide wax and 6 parts of plasticizer were mixed and added into an internal mixer, and mixed at 86°C for 2 minutes. Then 18 parts of filler, 1 part of antioxidant and 3 parts of reactive additive prepared in Example 2 were added, and mixed at 82°C for 4 minutes. Then 1 part of accelerator and 0.8 part of vulcanizing agent were added, and mixed at 55°C for 2 minutes. The jacket material was obtained by cooling the discharged material.
[0038] The filler is aluminum hydroxide, white carbon black and hydrotalcite mixed in a mass ratio of 3:2:1. The plasticizer is polypropylene adipate; the antioxidant is antioxidant 1010; the accelerator is accelerator TMTD; and the vulcanizer is 2,4-dichlorobenzoyl peroxide.
[0039] Example 4
[0040] Preparation of sheath material:
[0041] 100 parts of chloroprene rubber, 11 parts of polyethylene, 8 parts of polyamide wax and 8 parts of plasticizer were mixed and added into an internal mixer, and mixed at 87°C for 3 minutes. Then 19 parts of filler, 1 part of antioxidant and 4 parts of reactive additive prepared in Example 2 were added, and mixed at 85°C for 5 minutes. Then 1-2 parts of accelerator and 0.8-1 part of vulcanizing agent were added, and mixed at 60°C for 3 minutes. The jacket material was obtained by cooling the discharged material.
[0042] The filler is aluminum hydroxide, white carbon black and hydrotalcite mixed in a mass ratio of 3:2:1. The plasticizer is polypropylene adipate; the antioxidant is antioxidant 1010; the accelerator is accelerator TMTD; and the vulcanizer is 2,4-dichlorobenzoyl peroxide.
[0043] Example 5
[0044] Preparation of sheath material:
[0045] 100 parts of chloroprene rubber, 12 parts of polyethylene, 9 parts of polyamide wax and 10 parts of plasticizer were mixed and added into an internal mixer, and mixed for 4 minutes at 88°C. Then 20 parts of filler, 2 parts of antioxidant and 5 parts of reactive additive prepared in Example 2 were added, and mixed for 5 minutes at 90°C. Then 2 parts of accelerator and 1 part of vulcanizing agent were added, and mixed for 3 minutes at 60°C. The jacket material was obtained after the material was discharged and cooled.
[0046] The filler is aluminum hydroxide, white carbon black and hydrotalcite mixed in a mass ratio of 3:2:1. The plasticizer is polypropylene adipate; the antioxidant is antioxidant 1010; the accelerator is accelerator TMTD; and the vulcanizer is 2,4-dichlorobenzoyl peroxide.
[0047] Comparative Example 2
[0048] Compared with Example 5, no reactive additive is added, and the remaining raw materials and preparation process remain the same as those of Example 5.
[0049] The sheath materials prepared in Examples 3-5 and Comparative Example 2 were tested; the tensile strength (GB528-92) and tear strength (GB530-81) were tested, and then a 3.5% by mass sodium chloride solution was prepared, added to the prepared sheath materials, and immersed for 60 days to test the changes in tensile strength and elongation at break.
[0050] The test results are shown in Table 1 below:
[0051] Table 1
[0052] Example 3 Example 4 Example 5 Comparative Example 2 Tensile strength / MPa 12.4 12.4 12.5 6.5 Tear strength / (KN / m) 42 42 43 24 Tensile strength reduction rate / % 2.3 2.1 2.0 10.1 Tear strength reduction rate / % 1.1 1.1 0.9 5.4
[0053] From the test results, it can be seen that the water resistance of the cable prepared by the present invention is good, which is beneficial to improving the service life of the cable.
[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A heating power cable, comprising a PTC core tape, an insulating layer and a sheath layer; the PTC material is wound around parallel metal wire cores to form a flat tape, the PTC core tape is wrapped with an insulating layer, and the insulating layer is wrapped with a sheath material to form a sheath layer; characterized in that: The sheath material is prepared by the following steps: The chloroprene rubber, polyethylene, polyamide wax and plasticizer are mixed and added into an internal mixer, and mixed at 86-88°C for 2-4 minutes, and fillers, antioxidants and reactive additives are added, and mixed at 82-90°C for 4-5 minutes; then accelerators and vulcanizers are added, and mixed at 55-60°C for 2-3 minutes, and the jacket material is obtained by cooling the material; by weight, the chloroprene rubber is 100 parts, the polyethylene is 10-12 parts, the polyamide wax is 6-9 parts, the plasticizer is 6-10 parts, the filler is 18-20 parts, the antioxidant is 1-2 parts, the reactive additive is 3-5 parts, the accelerator is 1-2 parts and the vulcanizer is 0.8-1 parts; The reactive additive is prepared by the following steps: Step 1: Mix allyl 1H, 1H-perfluorooctyl ether, glacial acetic acid, toluene and solid acid, heat to 60°C, add hydrogen peroxide, keep the temperature unchanged after the addition, continue stirring and reacting for 6 hours to obtain a fluorine-containing auxiliary agent; the molar ratio of allyl 1H, 1H-perfluorooctyl ether, glacial acetic acid and hydrogen peroxide is 0.1:0.15:0.2; the mass ratio of allyl 1H, 1H-perfluorooctyl ether, toluene and solid acid is 1:5:0.4; Step 2: Add aminopolysiloxane and fluorine-containing additives to isopropanol, stir and react at 80° C. for 5 hours to obtain a reactive additive; the mass ratio of aminopolysiloxane, fluorine-containing additive and isopropanol is 8:1.6:
15.
2. A heating power cable according to claim 1, characterized in that: The PTC material is prepared by the following steps: By weight, 30 parts of polypropylene, 30 parts of polyvinylidene fluoride, 3 parts of aluminum hydroxide, 3 parts of magnesium oxide, 6 parts of additives, 1 part of antioxidant MB and 1 part of antioxidant 168 are mixed evenly, and then 65 parts of carbon nanotubes are added for mixing, the mixing temperature is 190-200°C, and the mixing time is 10-12min; then, the material is pressed and formed at 185±5°C to obtain a PTC material; the additives are lauric acid and ethylene-vinyl acetate copolymer, and the mass ratio of the additives is 1:
3.
3. A heating power cable according to claim 1, characterized in that: The filler is a mixture of aluminum hydroxide, white carbon black and hydrotalcite in a mass ratio of 3:2:
1.
4. A heating power cable according to claim 1, characterized in that: The plasticizer is polypropylene adipate; the antioxidant is antioxidant 1010; the accelerator is accelerator TMTD, and the vulcanizing agent is 2,4-dichlorobenzoyl peroxide.
Citation Information
Patent Citations
High-thermal conductivity polymer sheath material for irradiation crosslinking heating of cable and preparation method thereof
CN104479230A
Anti-aging flame-retardant cable insulating material and preparation method thereof
CN113174094A